Perancangan Ontologi Semantik: Representasi Digital Kuliner Khas Pulau Dewata - Wiguna, I Putu Agus Arya; Putra, I Gusti Ngurah Anom Cahyadi (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2023)
Advances in information technology are currently driving the growth of the number of internet users. In the business world, the role of technology is very important, and it can be said that it has become a primary need for entrepreneurs at this time. Likewise about culinary, knowledge about this needs to be taken and judged properly digitally such as from the aspect of place, taste, presentation and price. So that later it can be given to the community and passed down from generation to generation as well as to promote to foreign tourists so that they can be better known and increase the country's foreign exchange. The use of ontology as an information representation technique is the preferred solution in this case because ontology can be used to improve the development of semantic applications, especially when dealing with the semantic web. The method of building the ontology model used is Methodology. This method is one method of building an ontology model that can reuse the built ontology for further system development. The development of the ontology model in this study uses an application called Protégé and in the evaluation process, the ontology gives good results in answering the questions given by the users.